P-Laplacian Dirac system on time scales. Issue 1 (11th December 2019) - Gulsen, Tuba; Yilmaz, Emrah; Kayali, Meltem
ABSTRACT: The -Laplacian type Dirac systems are nonlinear generalizations of the classical Dirac systems. They can be observed as a bridge between nonlinear systems and linear systems. The purpose of this study is to consider -Laplacian Dirac boundary value problem on an arbitrary time scale to get forceful results by examining some spectral properties of this problem on time scales. Interesting enough, the -Laplacian type Dirac boundary value problem exhibits the classical Dirac problem on time scales. Moreover, we prove Picone's identity for -Laplacian type Dirac system which is an important tool to prove oscillation criteria on time scales. It generalizes a classical and well-known theorem for to general case